2016
DOI: 10.1016/j.fuel.2016.05.061
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Marcellus Shale and Huntersville Chert before and after exposure to hydraulic fracturing fluid via feature relocation using field-emission scanning electron microscopy

Abstract: a b s t r a c tTwo sets of experimental in situ fluid-rock interaction studies were implemented to understand the interactions between hydraulic fracturing fluid and rocks of the Marcellus Shale gas play. Marcellus Shale and Huntersville Chert core samples were exposed to synthetically prepared fracturing fluid and recycled fracturing fluid from the field, respectively, and examined before and after in situ exposure using surface relocation techniques via high-resolution field-emission scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 21 publications
1
64
0
Order By: Relevance
“…For system with additional Ba 2+ and SO4 2-, 2 mM BaCl2 and 0.06 mM Na2SO4 were added to the fracture fluid. The concentration of BaCl2 was based on the Ba concentration measured from flowback water (Dieterich et al 2016), and the concentration of Na2SO4 was used to generate a solution mildly saturated with respected to barite. The saturation index for barite was log10(Q/Ksp) = 1.3, where Q is the ion activity product of Ba 2+ and SO4 2-, and Ksp is the solubility product for barite under the reaction condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For system with additional Ba 2+ and SO4 2-, 2 mM BaCl2 and 0.06 mM Na2SO4 were added to the fracture fluid. The concentration of BaCl2 was based on the Ba concentration measured from flowback water (Dieterich et al 2016), and the concentration of Na2SO4 was used to generate a solution mildly saturated with respected to barite. The saturation index for barite was log10(Q/Ksp) = 1.3, where Q is the ion activity product of Ba 2+ and SO4 2-, and Ksp is the solubility product for barite under the reaction condition.…”
Section: Methodsmentioning
confidence: 99%
“…Existing studies have focused mostly on shale fracture surfaces, sand and chip surfaces, and evolution of aqueous fluids. These studies have shown that important shale chemical reactions include the dissolution of primary minerals such as carbonate and pyrite, and precipitation of secondary minerals such as carbonate, sulfate, and (hydr)oxides (Grieser et al 2007, Pournik et al 2014, Dieterich et al 2016, Marcon et al 2017, Vankeuren et al 2017. Although these studies provide insights to gas/oil and fluid transport behavior through fractures, they cannot be readily applied to estimating chemical alterations more than tens of micrometers into the shale matrix.…”
Section: Introductionmentioning
confidence: 99%
“…These fluids can generate dissolved pores on the rock surface, thus enhancing the flow conductivity of the shale formation and increasing communication among the flowing channels. Moreover, the dissolution of feldspar may also consume huge amounts of water on the basis of the reaction 6 ⇔ 3 [47,48] although more quantitative work on this remains to be made.…”
Section: Effect Of Time On Hydrationmentioning
confidence: 99%
“…Moreover, the dissolution of feldspar may also consume huge amounts of water on the basis of the reaction. KAISiO 8 + 6H 2 O + H + ⇔ AIO(OH) + 3H 4 SiO 4 + K + [47,48] although more quantitative work on this remains to be made.…”
Section: Effect Of Temperature On Hydrationmentioning
confidence: 99%
“…mineral liberation) or phase purity from core samples or grinded mate-rial (Van der Wal and Kruseman, 2011). The advantages of automated systems like the QEMSCAN ® (Quantitative Evaluation of Minerals by Scanning Electron Microscopy) are their statically robustness, reliable mineral identifications, round-the-clock operations, high throughput, multiple applications with high degree of flexibility, multiple measurements modes, built-in quality-control programs, and data/information (Fennel et al, 2005;Ayling et al, 2012) that can be used in several fields as forensics, environmental geology, coal and petroleum mineralogy, geopolymer development, meteorite investigations or archaeological research (e.g., Al-Otoom et al, 2005;Goodall and Scales, 2007;Chen-Tan et al, 2009;Pirrie et al, 2009;Segvic et al, 2014;Menzies et al, 2015;Dieterich et al, 2016;Mackay et al, 2016;McLeod et al, 2016). The energy-dispersive X-ray spectroscopy (EDS)-SEM systems, such as the QEMSCAN ® , have made great progress in speed and precision since the beginning of the 21st century, becoming a reference system for quantitative evaluation of minerals by scanning electron microscopy, which was originally designed for the mining industry (e.g., Camm et al, 2004;Liu et al, 2005;Goodall and Scales, 2007;Pascoe et al, 2007;Rollinson et al, 2011;Santoro et al, 2014;Anderson et al, 2014), although it has been gaining recognition in other areas of research (e.g., Butcher et al, 2003;Pirrie et al, 2004;Al-Otoom et al, 2005;Sliwinski et al, 2009;Šegvić et al, 2014;Potter-McIntyre et al, 2014).…”
Section: Introductionmentioning
confidence: 99%